Business model innovation for digital health entrepreneurship in primary healthcare in South Africa - Chindongo, Dalitso (University of the Witwatersrand, Johannesburg, 2024)
Introduction and Background: The study investigates the real-life encounters of entrepreneurs in the digital health sector in South Africa, with a focus on their innovative approaches in improving primary healthcare services. It compares seven different digital health ventures (A - G), and explores the challenges related to accessing high quality healthcare, examining how incorporating digital health technologies (DHTs) and developing creative business models is improving Primary Healthcare services in South Africa. Research Problem and Objectives: The central research question examines how digital health entrepreneurs can enhance the accessibility and quality of healthcare services through innovative business models, thereby addressing the challenges identified in primary healthcare. Methodology: For this research a qualitative approach was taken, involving a multiple case study of the seven digital health ventures operating in South Africa. The data collection comprised semi-structured interviews with CEOs/Founders and performing document analysis. The Business Model Canvas and Systems Thinking frameworks were employed in analyzing the gathered data. Key Findings: Accessing Quality Healthcare Challenges: Digital health ventures are tackling geographical and socio-economic challenges through telehealth and mobile health (mHealth solutions). Real world experiences demonstrate how these digital health ventures connect healthcare professionals with specialists, enhancing access for rural and underserved areas that make use of Primary Healthcare services in South Africa. iii The focus is on personalized and community specific interventions that prioritize patient centered care adapted to local settings, going beyond the generic digital health tools analysed in existing literature on digital health entrepreneurship. The incorporation of Digital Health Technologies (DHTs) The digital health ventures demonstrate real world use cases of DHTs like using AI based analysis, for treatment and telehealth for monitoring from a distance. These uses are in line with. going beyond the knowledge found in current research on Digital Health. Research results illustrate the significance of customizing DHT implementations to address community requirements shedding light on the obstacles and possibilities of merging technologies, in various healthcare settings. Innovative Business Models: The digital health ventures employ unique and customized revenue models, such as subscription fees and strategic partnerships, that go beyond the generic models discussed in the literature. Case studies based on the digital health ventures, illustrate the practicalities of partnership models, showcasing collaborations with healthcare providers and public health organizations, which enhance the understanding of business model adaptability in the digital health ecosystem. Conclusions and Implications: The study concludes that innovating business models, in primary healthcare could transform healthcare services in South Africa. Digital health entrepreneurship not only improves primary healthcare outcomes, but also enhances patient engagement. The research also emphasizes the significance of forming partnerships, establishing sustainable revenue models, and implementing supportive policies to maximize the advantages of digital health solutions.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital health; Primary healthcare; Business model innovation; Telemedicine; mHealth; South Africa; UCTD; SDG-9: Industry, innovation and infrastructure